(untitled) (International Journal of Engineering and Computer Science, 2014)
A sensor network is one of the most adaptive research area that requires the optimization in term of energy effectiveness, load balancing etc. The sensor network is defined under the particular localization architecture and having the challenges in terms of load minimization, energy loss reduction, security etc. One of such common and most adaptive research problem is routing. In this paper, optimization is provided to the one of the effective routing algorithm called minimum-hop routing. As the communication is performed, each participating node in the network losses some amount of energy. The minimum hop routing, generates an energy effective path to perform the communication. But this effective path increases the load on the selective hops of defined routing approach. Because of which, the hops of this routing path dies earlier to other nodes. The technique proposed in this paper is the improvement to minimum hop routing by identifying the optimal compromising nodes to the minimum-hop routing path nodes.